Review on Phytosome for Topical Drug Delivery - Mandwe S. Vrushabh,; Dr. Sandeep C. Atram,; Bawankar V. Dipali,; Bhonde G. Akash,; Puri G. Ashutosh, (Asian Journal of Pharmaceutical Research and Development, 2025)
In recent years, medicinal herbs and their constituent phytochemicals have gained considerable attention as promising therapeutic agents for various diseases. Nevertheless, limitations such as low bioavailability and insufficient selectivity may hinder their clinical efficacy. Consequently, enhancing bioavailability remains a critical challenge for improving the therapeutic potential of dietary phytochemicals. To address this, phytosome-based nanotechnology represents a significant advancement in the field of drug delivery, particularly in enhancing the topical administration of bioactive phytochemicals. To improve the absorption and inadequate permeability of phytochemicals across biological barriers, such as the skin. Phytosomes, as lipid-based nanoscale carriers, play a pivotal role in improving the pharmacokinetic and pharmacodynamic profiles of polyphenolic compounds derived from herbal sources. In this review we focus on the delivery of phytochemicals by topical route by encapsulating them in phyto-phospholipid complex, which is phytosome to improve absorption and bioavailability and penetrate the biological membrane easily.